STUDENTS’ PERCEPTION OF EXTENSIVE READING ACTIVITY THROUGH READING LOG - - Gabriella; Veronica L. Diptoadi (Magister Scientiae, 2019)
As prospective English teachers, the students of the English department are expected to have sufficient English proficiency especially reading skills since most of the resources in the learning process are printed in English. Responding to the previous demand, the English Department provides a supplementary activity for developing the students’ reading skills. Hence, the focus of this study is on investigating how the students perceived the role of extensive reading activity in Reading A course in motivating them to read more in order to improve their reading skills as well as to enhance other skills and components, such as writing, speaking, and vocabulary. The questionnaire was answered by 29 students to find out their perception on extensive reading activity in Reading A course during the academic year of 2017/2018. In addition to the questionnaire, the lecturer of the course was also interviewed to confirm the students’ responses. After the data analysis, it was discovered that the students’ perception on extensive reading activity was positive.